PSVIII-11 In Vitro Incubation with a Bacillus-Based Direct-fed Microbial Improves Starch Digestibility. (21st September 2022) - Pan, Liyi; Harper, Karen; Cappellozza, Bruno; Copani, Giuseppe; Queiroz, Oscar
Abstract: Besides being well-recognized as a probiotic to human and livestock species, Bacillus spp. are also able to secrete a wide range of enzymes that improve carbohydrate, protein, and lipid digestibility, which in turn, will lead to greater milk yield and growth performance in dairy and beef cattle, respectively. Hence, we hypothesized that the incubation of a Bacillus-based direct-fed microbials (DFM) solution would improve in vitro starch digestibility (IVSD) in different concentrates (two barley sources, corn, sorghum, and wheat; starch content = 41.1 to 72.5% DM). Therefore, our objective was to evaluate the effects of incubating a Bacillus-based DFM on IVSD of these concentrates over a 12-h period. Concentrates were incubated, in triplicates, into the media containing (DFM) or not (CON) the DFM (Bacillus licheniformis and B. subtilis; 3.2 × 10 9 CFU/g; Bovacillus, Chr. Hansen A/S, Horsholm, Denmark) over a 12-h period, whereas IVSD was evaluated at 6- and 12-h post-DFM incubation. Ruminal IVSD on dried 1-mm screen ground samples was determined using procedures previously described and validated. All data were analyzed using SAS. Incubation of a Bacillus-based DFM increased mean IVSD in all samples (P ≤ 0.01) analyzed herein, with the greatest overall improvement observed in low-density barley (18.2%) and sorghum (13.6%). Treatment × hour interactions were observed in 3 out 5 concentrates (P ≤ 0.001). In general, incubation with a DFM improved 6-h IVSD (P ≤ 0.02), ranging from 6.7 (wheat) to 67.8% (low-density barley), whereas 12-h IVSD was also greater in wheat inoculated with DFM (14.9% increase vs. CON; P < 0.0001). In summary, incubation of a Bacillus-based DFM improved in vitro starch digestibility in 5 out 6 concentrate sources, with most of the improvements within 6-h. These results highlight the ability of Bacillus spp. in releasing enzymes that degrade carbohydrates, likely benefiting production parameters of livestock.